Quality of life of grown-up congenital heart disease patients after congenital cardiac surgery - Loup, Ophélie; von Weissenfluh, Catherina; Gahl, Brigitta; Schwerzmann, Markus; Carrel, Thierry; Kadner, Alexander (European journal of cardio-thoracic surgery, 2009)
Due to better early and long-term outcome, the increasing population of grown-ups with congenital heart disease (GUCH) brings up unexpected quality of life (QoL) issues. The cardiac lesion by itself is not always the major problem for these patients, since issues pertaining to QoL and psychosocial aspects often predominate. This study analyses the QoL of GUCH patients after cardiac surgery and the possible impact of medical and psychosocial complications. A questionnaire package containing the SF-36 health survey (health related QoL), the HADS test (anxiety/depression aspects) and an additional disease specific questionnaire was sent to 345 patients (mean 26+/-11 years) operated for isolated transposition of the great arteries (TGA), tetralogy of Fallot (TOF), and ventricular septal defect (VSD). The scores were compared with age- and gender-matched standard population data and in relation to the underlying congenital heart disease (CHD). In all SF-36 and HADS health dimensions the GUCH patients showed excellent scores (116+/-20), which are comparable to the standard population (100+/-15), regardless of the initial CHD (p=0.12). Eighty-two percent of the patients were found to be in NYHA class I and 83% patients declared that they do not consider their QoL to be limited by their malformation. Complications like reoperations (p=0.21) and arrhythmias (p=0.10) do not show significant impact on the QoL. The additional questionnaire revealed that 76% of adult patients have a fulltime job, 18% receive a full or partial disability pension, 21% reported problems with insurances, most of them regarding health insurances (67%), and 4.4% of adult patients declared to have renounced the idea of having children due to their cardiac malformation. QoL in GUCH patients following surgical repair of isolated TOF, TGA and VSD is excellent and comparable to standard population, this without significant difference between the diagnosis groups. However, these patients are exposed to a high rate of complications and special psychosocial problems, which are not assessed by standardized questionnaires, such as the SF-36 and HADS. These findings highlight the great importance for a multidisciplinary and specialized follow-up for an adequate management of these complex patients.